Two new species of Merogomphus Martin, 1904 (Odonata: Anisoptera: Gomphidae) from the Western Ghats, India - Chandran, Ayikkara Vivek; Sawant, Dattaprasad; Chandran, Reji; Koparde, Pankaj; Jose, Subin Kaniyamattathil; Kunte, Krushnamegh (Zootaxa, 2025)
We describe two new species of dragonflies from the Western Ghats Biodiversity Hotspot, Merogomphus aryanadensis sp. nov. from Kerala and M. flavoreductus sp. nov. from Maharashtra, India. Morphologically, these species are closely aligned with M. tamaracherriensis Fraser, 1931, an endemic species of the Western Ghats; however, they are distinguished by unique features in their caudal appendages, accessory genitalia, and body markings. Additionally, both species are considerably smaller than other known Merogomphus spp. found in India. The differential diagnosis presented includes a comprehensive morphological photographic assessment of the two new species described and their two endemic congeners, also from the Western Ghats. We also establish a significant genetic distance between these newly described Merogomphus species and M. tamaracherriensis.